Resting-State Functional Connectivity of the Thalamus in Complete Spinal Cord Injury. (February 2020) - Karunakaran, Keerthana Deepti; Yuan, Rui; He, Jie; Zhao, Jian; Cui, Jian-Ling; Zang, Yu-Feng; Zhang, Zhong; Alvarez, Tara L.; Biswal, Bharat B.
Background . Neuroimaging studies of spinal cord injury (SCI) have mostly examined the functional organization of the cortex, with only limited focus on the subcortical substrates of the injury. However, thalamus is an important modulator and sensory relay that requires investigation at a subnuclei level to gain insight into the neuroplasticity following SCI. Objective . To use resting-state functional magnetic resonance imaging to examine the functional connectivity (FC) of thalamic subnuclei in complete SCI patients. Methods . A seed-based connectivity analysis was applied for 3 thalamic subnuclei: pulvinar, mediodorsal, and ventrolateral nucleus in each hemisphere. A nonparametric 2-sample t test with permutations was applied for each of the 6 thalamic seeds to compute FC differences between 22 healthy controls and 19 complete SCI patients with paraplegia. Results . Connectivity analysis showed a decrease in the FC of the bilateral mediodorsal nucleus with right superior temporal gyrus and anterior cingulate cortex in the SCI group. Similarly, the left ventrolateral nucleus exhibited decreased FC with left superior temporal gyrus in SCI group. In contrast, left pulvinar nucleus demonstrated an increase in FC with left inferior frontal gyrus and left inferior parietal lobule in SCI group. Our findings also indicate a negative relationship between postinjury durations and thalamic FC to regions of sensorimotor and visual cortices, where longer postinjury durations (~12 months) is associated with higher negative connectivity between these regions. Conclusion . This study provides evidence for reorganization in the thalamocortical connections known to be involved in multisensory integration and affective processing, with possible implications in the generation of sensory abnormalities after SCI.